Analisis Kontribusi Tenaga Kerja Perempuan pada Pertanian Padi Tadah Hujan di Desa Setiris Kecamatan Maro Sebo - Santi Marina; Yusma Damayanti; Riri Oktari Ulma (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study fully reveals the role of women in rainfed rice farming in Setiris Village, Maro Sebo District. This study aimed to determine the picture of rainfed rice farming in Setiris Village, Maro Sebo District, as well as the role of women in agriculture and the variables that influence this role. A total of 25 respondents from 2 farmer groups participated in the survey conducted in January and February 2024. A total of 10 respondents came from Lopak Serapil and 15 from Tanjung Harapan. The factors studied were the number of family dependents (X1), planting area (X2), farming experience (X3), side jobs (D1), female farmer toddlers (D2), and female labor contribution (Y). Multiple Linear Regression using SPSS 26 software was the analysis instrument used. According to the research results, in Setiris Village, Maro Sebo District, rainfed rice farming activities include land preparation, planting, fertilizing, weeding, harvesting, controlling pests and plant diseases, and seeding. Female labor provides 41.69 HOK/planting season, or 81% of the total working hours, with planting area, farming experience, and family responsibilities being the main influencing factors. Based on multiple linear regression analysis, all of these factors simultaneously affect the contribution of women's work, with a significance value of f-statistic 0.000 smaller than ⁰ = 0.05 (<0.05). However, the significance values ​​for the variables number of family dependents (0.002), planting area (0.005), and farming experience (0.021) are all smaller than ⁰ = 0.05 (<0.05). Thus, the contribution of female labor to rainfed rice farming in Setiris Village, Maro Sebo District, is influenced by these factors.